Meta-analytic evidence for a sex-diverging association between alcohol use and body mass index - Siegmann, Eva-Maria; Mazza, Massimiliano; Weinland, Christian; Kiefer, Falk; Kornhuber, Johannes; Mühle, Christiane; Lenz, Bernd (Scientific reports, 2022)
Alcohol use is an important health issue and has been suggested to contribute to the burden produced by obesity. Both alcohol use and obesity are subject to sex differences. The available studies on the relationship between alcohol use and body mass index (BMI) report inconsistent results with positive, negative, and null findings which requests a meta-analytic approach. Therefore, we conducted a meta-analysis of case-control, cohort, and cross-sectional studies. The systematic literature search and data extraction was performed by 3 independent raters. We conducted sex-separated meta-analyses and -regressions to investigate how alcohol consumption associates with BMI. Our systematic literature search resulted in 36 studies with 48 data sets (Nmen = 172,254; kmen = 30; Nwomen = 24,164; kwomen = 18; Nunknown sex = 672,344; kunknown sex = 24). Alcohol use was associated with higher BMI in men (g = 0.08 [0.07; 0.09]) and lower BMI in women (g = − 0.26 [− 0.29; − 0.22]). Moreover, we found the amount of daily alcohol intake in men (β = 0.001 [0.0008; 0.0014]) and ethnicity in women (g[Caucasians] = − 0.45 versus g[Asians] = − 0.05; z = 11.5, p < 0.0001) to moderate these effects. We here identified sex-diverging relationships between alcohol use and BMI, found daily alcohol intake and ethnicity to sex-specifically moderate these effects, and argue that sex-specific choice of beverage type and higher amount of daily alcohol use in men than in women account for these observations. Future research is needed to provide empirical evidence for the underlying mechanisms.
Veröffentlicht: 19. Dezember 2022
Gesehen am 21.07.2023